Convection of snow: when and why does it happen? - Jafari, Mahdi; Lehning, Michael (Frontiers in Earth Science, 2023)
Convection of water vapor in snowpacks is supposed to have a major impact on snow density and microstructure profiles with strong implications for the thermal regime and snow stability. However, the process has never been directly measured and only recently been simulated for idealized conditions. The analysis suggests that natural convection is not likely to happen in typical horizontally homogeneous polar or Alpine snow covers. This paper studies the potential impact of heterogeneity induced e.g. by shrubs on convection of water vapor. We find that natural convection triggered by buoyancy occurs even with sub-critical Rayleigh number as low as 5 due to heterogeneity in snow density. This leads to complementing contributions of diffusive and convective flux divergence on snow density changes. The combined effect of diffusion and convection helps to generate the often-observed low density foot and high-density top of e.g. Arctic snowpacks. The strongest effect of convection is not for very thin or thick snow covers but for snow covers with thickness in the order of 0.5 m. This scale facilitates the development of convection cells. Further work should address the additional effects of sub-snow lateral temperature variations and assess the effect of convective vapor fluxes on snow microstructure.